2012
DOI: 10.1117/1.jbo.18.6.061213
|View full text |Cite
|
Sign up to set email alerts
|

In vivoassessment of human burn scars through automated quantification of vascularity using optical coherence tomography

Abstract: In scars arising from burns, objective assessment of vascularity is important in the early identification of pathological scarring, and in the assessment of progression and treatment response. We demonstrate the first clinical assessment and automated quantification of vascularity in cutaneous burn scars of human patients in vivo that uses optical coherence tomography (OCT). Scar microvasculature was delineated in three-dimensional OCT images using speckle decorrelation. The diameter and area density of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 55 publications
1
77
0
Order By: Relevance
“…Nevertheless,only subjective scores are available and objective parameters are missing [37, 38]. Moreover, scars after burn injury were objectively explored with OCT by Gong et al [37, 39] and Liew et al [40] through automated quantification of the density and diameter of the vasculature using speckle decorrelation and the attenuation coefficient [37, 39, 40]. The result is that inside the scar tissue the density of blood vessels is increased and that there is no typical vascular network formation like in healthy skin, but a parallel organization of the vasculature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless,only subjective scores are available and objective parameters are missing [37, 38]. Moreover, scars after burn injury were objectively explored with OCT by Gong et al [37, 39] and Liew et al [40] through automated quantification of the density and diameter of the vasculature using speckle decorrelation and the attenuation coefficient [37, 39, 40]. The result is that inside the scar tissue the density of blood vessels is increased and that there is no typical vascular network formation like in healthy skin, but a parallel organization of the vasculature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When a hypertrophic scar occurs, these cutaneous injuries lead to the production of excess collagen synthesis and local vascular proliferation [22,17]. Three studies used OCT to evaluate changes in skin fibrosis due to burn scars, hypertrophic scars, and various scar types pre- and post-laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study used OCT to quantify the vascularity of hypertrophic scars in 8 patients and found an increased mean vascular density in hypertrophic scar tissue (38%) when compared with normal, unscarred skin (22%) [17]. The study revealed there was a proliferation of larger vessels (diameter ≥ 100 μm) in hypertrophic scars that was absent from normal scars and normal skin [17]. This study demonstrates OCT’s assessment of vascularity may aid in diagnosis and monitoring of response to therapy in hypertrophic scars.…”
Section: Discussionmentioning
confidence: 99%
“…Scars after burn injury have been investigated using D-OCT. Gong et al [42,43] and Liew et al [44] developed a speckle decorrelation OCT system and imaged scars [42,43,44]. They assessed the vasculature within the scars, the light attenuation coefficient of the tissue and the stiffness using OCT. Scars showed an increase in the number of blood vessels as well as disturbance in the vessel network compared to adjacent skin (fig.…”
Section: Inflammatory Conditionsmentioning
confidence: 99%